Kebijakan Program Indonesia Pintar (PIP): Mengukur Tantangan Implementasi, dan Kontribusinya terhadap Pemerataan Pendidikan di Indonesia (Pusat Riset dan Inovasi Nasional, 2026)
The national priority program of 12 years of compulsory education is a strategic effort by the government to improve the quality and equity of education, particularly at the secondary education level. This program is supported by the School Operational Assistance (BOS) and the Indonesia Smart Program (PIP). The PIP funds are used to meet the educational needs of students, such as purchasing books, stationery, uniforms, and transportation costs. The goal of providing PIP is to reduce the financial burden of education, decrease school dropout rates, and increase access to quality education. This study examines the effectiveness of PIP in promoting educational equity in Indonesia and evaluates the alignment of government policies related to beneficiaries, implementation, and monitoring of PIP. The method used is a literature review for public policy evaluation in the field of education. The findings show that PIP has successfully increased educational participation, as reflected in the improvement of the School Participation Rate (APS), Gross Participation Rate (APK), and Net Participation Rate (APM). PIP also expands educational access for children from low-income families. However, its implementation faces challenges such as bureaucratic obstacles, misidentification of recipients, low parental administrative literacy, and delays in the distribution of assistance in 3T regions (frontline, outermost, and underdeveloped).